“SEGUNDO TEMPO” PROGRAM PEDAGOGICAL FOLLOW-UP IN AGREEMENTS FROM BRAZIL NORTH AND NORTHEAST REGIONS (Fiep Bulletin - online, 2013)
A possibilidade de visitas periódicas e de assessoria à distância, amparada por uma proposta pedagógica consistente são os elementos facilitadores. Diante dos dados apresentados, conclui-se que, apesar das dificuldades relatadas, o trabalho desenvolvido pela EC 23 demonstra a importância do PST como política de acesso ao esporte e lazer às comunidades nas quais a vulnerabilidade social se mostra acentuada. This experience report aims to describe the activities developed by the Ministry of Sports Collaborative Team (CT) 23 acting along with nuclei in the states of Amapá, Pará, Maranhão and Piauí when training and following agreements from “Segundo Tempo” Program (PST). The distances between CT 23 and the program agreements and nuclei – both for standard PST and “Mais Educação” partnership with the Ministry of Education – are a great difficulty added to the lack of qualified professionals and communication systems. The possibility of periodical visitations and orientation from a distance supported by a consistent pedagogical proposal are facilitating elements. Towards data presented the conclusion is that despite the difficulties reported the work developed by CT 23 shows how relevant PST is as a policy for socially vulnerable communities to access sports and leisure.
Keywords: Pedagogical Follow-up; “Segundo Tempo” Program; Brazil North and Northeast Regions.